Strategi Transformasi Badan Kredit Desa (BKD) di Kabupaten Sidoarjo - Budi Dwi Santosa (Jurnal Aplikasi Manajemen, 2012)
Microfinance institutions are well accepted as an effective instrument in alleviating poverty. In Indonesia, microfinance institutions can be divided into two categories: (i) bank including BRI (Peoples’ Bank of Indonesia) and BPR (Credit Union Bank), and (ii) non-bank sectors such as Koperasi, Lembaga Dana dan Kredit Pedesaan (LDKP) and Badan Kredit Desa (BKD). LDKP gets formal legalizations from local government, while BKD supervised by BRI has also formal status from local government. Based on Surat Keputusan Bersama (SKB) published by four ministries, BKD should be transformed into three forms: BPR, Koperasi or Rural Government Enterprise (Badan Usaha Milik Desa/BUMdes).This paper provides background research for potential policies to contain BKD in dealing to institutional transformation and discusses (i) key indicators influencing microfinance institutional transformation, (ii) BKD practices associated with microfinance institutional regulations. An institutional economics framework suitable for analyzing these problems is developed and presented. Based on interviews, BKD transformations depend on five indicators: (i) instrument capitalization, (ii) decision process, (iii) business orientation, (iv) relationship with costumers and (v) business plan. There are three options in terms of BKD regulation. First, there are lack of capital and human resources, when BKD should be transformed into BPR or Koperasi. Second, when there is no change in BKD practices, local government (PEMDA) should be active in monitoring and evaluation to minimize moral hazard evidence. Third, when purpose of transformation is empowering BKD, transformation should be viewed as a long-term process, where BKD assosiation will play a crusial role in BKD practices.Keywords: microfinance, Badan Kredit Desa(BKD), institutional transformation, micro corporate governance